Nurturing moral community: A novel moral distress peer support navigator tool - Morley, Georgina (Nursing ethics, 2024)
Moral distress is a pervasive phenomenon in healthcare for which there is no straightforward “solution.” Rhetoric surrounding moral distress has shifted over time, with some scholars arguing that moral distress needs to be remedied, resolved, and eradicated, while others recognize that moral distress can have some positive value. The authors of this paper recognize that moral distress has value in its function as a warning sign, signaling the presence of an ethical issue related to patient care that requires deeper exploration, rather than evidencing identification of the “right” course of action. Once the experience of moral distress is identified, steps ought to be taken to clarify the moral issue, and, if possible and reasonable, the patient’s values ought to be prioritized. This paper offers concrete actions steps, drawn from theory, which can be used in clinical practice to provide peer support or to facilitate self-reflection for morally distressed individuals. This approach empowers morally distressed individuals to explore ethical issues, identify concrete steps that can be taken, and mitigate feelings of powerlessness that are often associated with moral-constraint distress. The questions guide individuals and peers to reflect first on the micro-space and then more broadly on the institutional culture, facilitating meso- and macro-reflection and action.